Development of work safety procedures for PCI Girder installation using interactive analysis models - Ahmad, Chairul; Fitri Nugraheni; Faisol (Teknisia, 2024)
As part of the government's infrastructure acceleration initiative, toll road construction has become a key focus to enhance regional development and connectivity. However, such projects, particularly those involving the installation of precast concrete girders, carry significant risks of workplace accidents. Between 2017 and 2021, six accidents related to girder erection occurred during toll road construction projects. This study aims to develop work safety procedures for the installation of Type I precast concrete girders in the Bakauheni–Sidomulyo toll road project. The proposed safety procedures, presented as a flow chart, are based on national and international safety standards, providing a clear and sequential overview of the process to ensure better understanding and risk mitigation. The study uses the Interactive Analysis Model for data analysis, encompassing Data Collection, Data Reduction, Data Presentation, and Conclusion Drawing, where data collection and analysis are conducted in an iterative and simultaneous manner. The results, validated by site engineers and safety officers both within and outside the project, identified 62 potential risks stemming from unsafe conditions and provided 85 safety recommendations. These findings offer practical guidance for contractors to minimize the risk of accidents during the PCI girder erection process.